The New Social Views on Police Brutality, Post George Floyd and Partisanship in the American Politics and Media - Abou bakr es seddiq BENSALAH, Imane GUERRA (My University, 2021)
This dissertation highlights an important issue which is police brutality against African Americans and how the death of George Floyd influenced political parties and the media. It evokes important questions on the nature of violence practiced against black community, it gives a truthful description of their long history of suffering from racism and brutality of law enforcement in America. This study will also highlights the different reactions to George Floyd protests from both Republicans and Democrats, this paper will contain an analysis of media coverage of the events that followed the tragedy .